Os muros do além: a construção do Cemitério do Alecrim e a (des)secularização da morte em NataL/RN - Tavares, Diogo Fontes de Souza (2016)
In the Catholic man from the city of Natal in the eighteenth hundreds, prevailed the idea that for a "right way" to heaven, it had to be met with certain practices that, if not done, the salvation would be uncertain. Living a life that is consistent to the ordering of the Church was necessary, but having a pompous funeral, ending in the atria of the church or in the brotherhood in which one was a member, was shown essential on the way to Paradise. However, these funeral traditions have become an obstacle to public health, because health workers - devised by European Enlightenment discourses - created that the the miasma (putrid exhalations of sick people and animals / dead) were disease vectors and demanded a cemetery away from where the living lived. From this premise, this research builds a narrative of how was this impasse in the then city of Natal in the nineteenth century, relying on reports and speeches of the provincial presidents, as well as decrees and health-hygienist character of policy measures (especially Imperial Decree of 1st October 1828 - which attributed the building of external cemeteries for burials), and data on the damage caused by Cholera morbus (a pandemic that swept spaces and arrived in Brazil in 1855). Based on this, we've analyzed these speeches and sanitary-hygienists measures supported by Enlightenment ideals and secularization, who aimed progress and hygiene standards for society, as part of a rational process and tended to reject the religion of social and political structure. Based on the ideas of Peter Berger and Danièle Herviu-Léger on secularization, the research uses historical documents (Province of Presidents Reports, Death Books, Official Gazettes, etc.), which are located in the History and Geography of Rio Grande do Norte Institute and the Public Collection of the Archdiocese of Natal to respond to building policy measure of the public cemetery of Alecrim was an exponent of death's secularization in the nineteenth century Natal. When working with these historical documents, and when these documents were read, it was noted that although the building of a public necropolis has been made, there was a possible boycott of the measure for people being buried there, which came to have been burials there when the Chapel was built on site, an act that Peter Berger conceptualizes as dessecularization.